Peranan Program Pojok Baca Berbasis Program Giat Literasi KM 6 Upaya Meningkatkan Nilai Literasi Siswa Kelas 5 SD Negeri Kerokan - Amalia, Fairuz Intan; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was motivated by a lack of literacy among students. The objectives of this research are (1) to describe the role of active literacy programs through reading corners, (2) to describe the results of AKM grades for grade 5 at SD Negeri Kerokan. The research method used is descriptive qualitative. The subject in this research is Kerokan State Elementary School. The techniques and data collection in this research used documentation studies, interviews and administering tests. The research results showed an increase of 6% obtained from pretest and posttest testing through Indonesian language subjects. The conclusion of the research that has been conducted shows that reading habits can influence the learning outcomes of class V students at Kerokan State Elementary School.